2015
DOI: 10.1007/s10847-015-0542-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of spray dried complexes of lutein with cyclodextrins

Abstract: Lutein (LUT) is one of the most important carotenoid and; the most prominent being its antioxidant activity. However, its use is limited due to poor solubility and instability under adverse conditions. An attempt is made to increase the solubility and hence bioavailability of LUT using various cyclodextrins viz., betacyclodextrin (bCD), hydroxypropyl betacyclodextrin (HP-bCD) and methyl betacyclodextrin (M-bCD). Physical mixtures and spray dried inclusion complexes were prepared and characterized using spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Figure 5 illustrates the Fourier transform infrared (FTIR) spectra of M. nitidum and its residue after liquefied DME extraction. A list of typical functional groups and IR signals with possible compounds was given earlier in the work by Kodama et al 26 The IR signal of lutein was reported by Nalawade et al 27 The typical changes in absorbance of lutein include CH 2 scissoring (1436 cm –1 ) and splitting due to lutein dimethyl groups (1361 cm –1 ) within the region from 1480 to 1360 cm –1 . The intensity of this absorbance reduced after DME extraction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure 5 illustrates the Fourier transform infrared (FTIR) spectra of M. nitidum and its residue after liquefied DME extraction. A list of typical functional groups and IR signals with possible compounds was given earlier in the work by Kodama et al 26 The IR signal of lutein was reported by Nalawade et al 27 The typical changes in absorbance of lutein include CH 2 scissoring (1436 cm –1 ) and splitting due to lutein dimethyl groups (1361 cm –1 ) within the region from 1480 to 1360 cm –1 . The intensity of this absorbance reduced after DME extraction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The -C=C-vibration peak was found at 1610 cm −1 [55]. In addition, the two peaks at 963 and 831 cm −1 were ascribed to the out of plane bending of -CH=CH-group of lutein [56,57]. Compared with the spectra of lutein and LDH, it was clearly that new characteristic peaks also appeared at 2856, 1609 and 1121 cm −1 due to the loading of lutein besides the typical characteristic peaks of LDH.…”
Section: Characterization Of Lutein/ldh Compositesmentioning
confidence: 89%
“…The influence of different independent variables, such as lutein, stevioside, β‐cyclodextrin, inlet air drying temperature, and feed rate, on the microparticle powder process were investigated using single‐factor experiments to select the significant ones and to determine their preliminary range. The effect of each variable was tested by changing it in a defined range, chosen according to the previous research literature (Álvarez‐Henao et al., 2018; Nalawade & Gajjar, 2015), while keeping the others fixed. In this study, values used in this preliminary screening were: lutein (200–1,000 mg), stevioside (100–800 mg), β‐cyclodextrin (1,500–3,500 mg), inlet air drying temperature (150–270°C), and feed rate (400–800 ml h −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Carotenoids combined with β‐cyclodextrin to form inclusion compounds can solve the defects of carotenoid stability, and can also be incorporated into aqueous solutions (Chen et al., 2007; Lima et al., 2016). The physiological and water‐soluble complexes of lutein and β‐cyclodextrin have been developed (Nalawade & Gajjar, 2015). For instance, the water‐dispersion and stability of lutein improved when encapsulated by methyl‐β‐cyclodextrin (Nalawade & Gajjar, 2015).…”
Section: Introductionmentioning
confidence: 99%